2015
DOI: 10.3892/or.2015.3865
|View full text |Cite
|
Sign up to set email alerts
|

Demethoxycurcumin induces the apoptosis of human lung cancer NCI-H460 cells through the mitochondrial-dependent pathway

Abstract: Abstract. Lung cancer is the most common cause of cancerrelated mortality in the US as well as other regions of the world. Curcumin, demethoxycurcumin (DMC) and bisdemethoxycurcumin (BDMC) are the major components of Curcuma longa L. It has been reported that curcumin inhibits the growth of various types of cancer cells in vitro and in vivo. However, the mechanisms involved in the inhibition of cell growth and induced apoptosis by DMC in human lung cancer cells remain unclear. In the present study, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…DMC induced G 2 /M cell cycle arrest and epigenetic changes in leukemia cells . Our previous study also showed that DMC induced the apoptosis of human lung cancer NCI‐H460 cells through the mitochondrial‐dependent pathway . BDMC inhibited adipogenesis in 3T3‐L1 preadipocytes and it had the potential to prevent obesity and induced cell apoptosis in human laryngeal carcinoma cells, activated hepatic stellate cells, and lung cancer NCI‐H460 cells .…”
Section: Introductionmentioning
confidence: 78%
“…DMC induced G 2 /M cell cycle arrest and epigenetic changes in leukemia cells . Our previous study also showed that DMC induced the apoptosis of human lung cancer NCI‐H460 cells through the mitochondrial‐dependent pathway . BDMC inhibited adipogenesis in 3T3‐L1 preadipocytes and it had the potential to prevent obesity and induced cell apoptosis in human laryngeal carcinoma cells, activated hepatic stellate cells, and lung cancer NCI‐H460 cells .…”
Section: Introductionmentioning
confidence: 78%
“…Therefore, novel treatment approaches for SCC are desperately needed. In an early study, Wu, Zhang, Yang, Ge, and Xin (2017) Ko, Lien, et al (2015) found that NCI-H460 cells treated with DMC were arrested in the S phase. Several studies have shown that cell death can be induced by increasing the expression of FAS/CD95 (Kumar, 2007;Wilson, 1998;Xu & Shi, 2007).…”
Section: Lung Cancermentioning
confidence: 99%
“…Several studies have shown that cell death can be induced by increasing the expression of FAS/CD95 (Kumar, 2007;Wilson, 1998;Xu & Shi, 2007). Ko, Lien, et al (2015) reported that in NCI-H460 cells treated with DMC, the level of FAS/ CD95 increased, which was accompanied by an increase in caspase-8…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to create novel, efficacious and harmless treatment methods. Curcumin (CUR), a polyphenol extracted from the herb turmeric, shows cytotoxicity in three main kinds of NSCLCs: adenocarcinoma [ 4 ], squamous [ 5 ] and large-cell cancers [ 6 ]. Furthermore, CUR shows no effects on normal cells or animal models tested at a high dose of up to 10 g per day [ 7 ].…”
Section: Introductionmentioning
confidence: 99%